Ammonia pollution in groundwater of Hanoi city and a case study for removal of ammonia by the zeolite adsorption process - Le Giao; Umita, Teruyuki; Samorn Muttamara; Sehested Hansen, Ian; Finnish International Development Agency(FINNIDA) (Bangkok : Asian Institute of Technology, 1995)
Presence of ammonia nitrogen in drinking water can cause accelerated corrosion of metals and materials used for water supply, affect chlorine disinfection efficiency and particularly it may cause a methaemoglobinaemia in infants through the oxidation to nitrate. In Hanoi city, approximately 218,000m3 of water, occupying 41% of the total city production, has been produced from ammonia polluted sources. The sources for nitrogen that may enter to groundwater table of Hanoi city could be wastewater, fertilizer, disposal of waste, and rainfall. The fertilizer source was the most significant generator of nitrogen with total amount of 73.4%, in which organic fertilizer is 95.8%. The results obtained from the study showed that the amount of nitrogen entered to the groundwater of whole city was about 1.25% of the total generated, in which about 0.97% was in the south of the city. Another potential source of ammonia in groundwater is peat land layers within the soil structure of Hanoi. Although the amount and characteristics of nitrogen generated from this source is unknown, a corelation between ammonia concentration in groundwater and peat land layers within soil structure was observed. Removal of ammonia from filtered effluent of Phap Van water plant was investigated, in which the A-4 synthetic zeolite of 8-12mesh was used for ion exchange media. An average ammonia removal of 87.4% was obtained from single column operations at a liquid flow rate of 5.1 L/hour. At a liquid flow rate of 7 .2 L/hour, an average ammonia removal of 81 .3% was observed. However, more than 4 mg/L of effluent ammonia concentration was observed when operating the system at 9.9 L/hour. An average ammonia removal of 91.9% was obtained from the mode of two columns in series with liquid flow rate of 7.2 L/hour, in which ammonia removed from the first column was 78% of the total. By using a solution of 2% NaCl with pH of 10.95 to extract adsorbed ammonia from loaded zeolite bed, approximately 96% of original exchange capacity of zeolite was regenerated at liquid flow rate of 7 .2 L/hour and a regeneration period of 1 hour. The cost estimations among the three available processes shown that zeolite adsorption process with a contact time of 0.73 minute is a most economic method for ammonia removal at Phap Van water treatment plant.
Thesis (M. Sc.) - Asian Institute of Technology, 1995
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Science
Keywords: Sewage -- Purification -- Adsorption